Implementation of Diagnostic Assessment on Fiqh Subjects - Muhammad Faiz; Anita Puji Astutik (At-Tarbiyat, 2023)
This research examines Diagnostic Assessment and its implementation in junior high schools. Islamic Religious Education subjects are one of the essential components in the school curriculum, and the quality of teaching can vary depending on various factors, including the school quality category. The research used a qualitative descriptive method and involved Islamic Religious Education teachers at SMP Muhammadiyah 9 Boarding School in Penatar Sewu Tanggulangin. The study aims to evaluate and understand the practice of Diagnostic Assessment and its implementation in junior high schools with B accreditation. This research also explores the perceptions of teachers, principals and students regarding this diagnostic assessment. The study uses a qualitative descriptive approach. The research subjects involved Islamic Religious Education teachers at SMP Muhammadiyah 9 Boarding School. Data was collected through interviews with school principals, teachers and students. The data analysis usually involves several stages, including data reduction, data presentation, and conclusion. This research shows that all educators in Islamic Religious Education subjects at the school have implemented diagnostic assessments before the learning process and by the regulations from the Ministry of Education and Culture in 2020. The implementation of diagnostic checks carried out by these educators takes the form of test sheets and student interviews. The conclusion of this research is that implementation and diagnostic assessments are not based on schools with good quality but depend on educators' understanding of the importance of these assessments, which Ismuba educators make in these schools implementing diagnostic checks to help students understand the material better and support achievement of learning objectives.